EFISIENSI PRODUKSI KOMODITAS LADA DI PROPINSI BANGKA BELITUNG - SYAM, AMIRUDDIN (SOCA: Jurnal Sosial Ekonomi Pertanian, 2012)
Most of Pepper farming in Indonesia is dominantly managed by small holders plantation that resulted its production currently tends to be low and stagnant. This condition has brought the producing Pepper as an export commodity to a question. Research on the Pepper production efficiency analyses and its factors influence was conducted to answer the question. The objective of the research is to study the Pepper farming performance and its production function included its production possibility frontier and which variables might influence the production function. The result shows that the Pepper farming is still profitable for the farmers. The Technical Efficiency (TE)) average of the sampled farmers is 0.71, means that to increase the Pepper production is still prospective. Meanwhile, the distribution of the TE shows that the Pepper does not have normal distribution. It means that there is still an opportunity to enhance its managerial capability as an internal factor influencing the Pepper production (process). In addition to the physical factors such as production inputs that influence the Pepper production, some other uncontrollable external factors i.e. climate and price are also involved in the Pepper production.
Keywords: Production, Efficiency, and Pepper. PENDAHULUAN